2012
DOI: 10.1159/000345829
|View full text |Cite
|
Sign up to set email alerts
|

Primary Tethered Cord Syndrome - Clinical and Urological Manifestations, Diagnosis and Management: A Prospective Study

Abstract: Primary tethered cord syndrome refers to a group of neural tube defects that are not externally obvious, and, if detected at an early age, surgical intervention may prevent the significant irreversible neurological deficits. This study was performed to evaluate the presenting clinical features of patients with primary tethered cord syndrome and the indications of surgery in such patients as well as the clinical and urological outcome. In all cases, the indication for surgery was the presence of a tethered cord… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 12 publications
0
13
0
Order By: Relevance
“…Urologic evaluation in OSD is an important component for treatment decisions and the gold standard remains UDS (cystometrography [CMG] and sphincter electromyography [EMG]). [33][34][35][36] When carefully performed, UDS yields information about lower urinary tract (LUT) function that guides neurosurgeons' decisions to operate and serves as a basis for comparison of surgical outcomes. 37 CMG reveals bladder reactivity when it is artificially filled and when it empties.…”
Section: Urologic Evaluation Of Patient With Suspected Osd and Tcsmentioning
confidence: 99%
“…Urologic evaluation in OSD is an important component for treatment decisions and the gold standard remains UDS (cystometrography [CMG] and sphincter electromyography [EMG]). [33][34][35][36] When carefully performed, UDS yields information about lower urinary tract (LUT) function that guides neurosurgeons' decisions to operate and serves as a basis for comparison of surgical outcomes. 37 CMG reveals bladder reactivity when it is artificially filled and when it empties.…”
Section: Urologic Evaluation Of Patient With Suspected Osd and Tcsmentioning
confidence: 99%
“…There was a slight female preponderance in this study group, consistent with findings of Kanev et al and Lad et al 6,7 However, more studies are needed to confirm this in the pediatric population as some studies indicate some variability in sex prevalence. 1,9 Additionally, multiple studies (including this analysis) have shown much greater prevalence in Caucasians/whites compared with other races and ethnicities (64.4%, Table 2). 7 Of the patients analyzed, 7.2% had complications following initial spinal laminectomy.…”
Section: Discussionmentioning
confidence: 75%
“…Such symptoms include neurogenic bladder, weakness, numbness, spasticity, spinal deformities, deformities in feet, and skin lesions. 1,4,9 Surgical release is an option that is widely practiced by pediatric neurosurgeons. From this descriptive analysis, we have identified patient age and the presence of comorbidities to be factors affecting surgical outcomes in children and adolescents undergoing surgical intervention for TCS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…8,9 There is a clear consensus that patients with tethered cord syndrome should be surgically untethered to prevent further deterioration, as a clinical response has been reported in 44 to 67%. 8,10 In view of the high occurrence of TSC in ARM patients and because of the fact that early symptoms of tethered cord syndrome, such as urinary incontinence, may be difficult to recognize in ARM patients due to associated anomalies of urogenital or renal origin, all ARM patients in our hospital are screened for TSC in the neonatal period using spinal ultrasonography. The aim of this study was to evaluate diagnosis and treatment of TSC in ARM patients by determining the sensitivity and specificity of spinal ultrasonography with MRI as the golden standard.…”
Section: Introductionmentioning
confidence: 99%